2020
DOI: 10.46576/english.v1i2.614
|View full text |Cite
|
Sign up to set email alerts
|

Construction of Islamic Character Education in Deli Malay Culture in Medan City

Abstract: Malay Deli is one of the Malay sub-groups who live in Medan City. This tribe has awealth of cultural values which are used as a basis for the formation of the characterof its people. Malay Deli is one of the tribes that combines tradition and teachings fromIslam, this is in accordance with the philosophy in their lives "Adat Bersendi Syarak,Syarak Bersendi Kitabullah. Melalyu Deli people construct religious and culturalvalues through several stages, namely: (1) education; (2) Imitation; (3) Habituation;(4) Mot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…In the opinion of Nemon and Hashmi, the Islamic tradition is quite comprehensive, such that respect for visitors and the provision of the finest meals for guests are expressed in great detail (Memon, 2020). Malay Deli culture in the city of Medan, for instance, is steeped in Islamic values such as always showing respect to visitors and placing courtesy above all else (Hidayat et al, 2020;Nurhadi, 2020)…”
Section: Morals To Guestsmentioning
confidence: 99%
“…In the opinion of Nemon and Hashmi, the Islamic tradition is quite comprehensive, such that respect for visitors and the provision of the finest meals for guests are expressed in great detail (Memon, 2020). Malay Deli culture in the city of Medan, for instance, is steeped in Islamic values such as always showing respect to visitors and placing courtesy above all else (Hidayat et al, 2020;Nurhadi, 2020)…”
Section: Morals To Guestsmentioning
confidence: 99%
“…The pesantren tradition has a significant influence in shaping the character of the santri and Indonesia. (Hidayat et al, 2020) The basic principles of educational practice in Islamic boarding schools do not recognize the concept of human superiority. (Halim, 2005)The principle of pesantren education teaches that humans have the same position before Allah, and that what distinguishes them is charity as a form of piety.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have reported the recently declining students' morals as evidenced by students' habit of spending more time on activities that are less useful, such as hanging out on the side of the road with their group of friends, spending more time on smartphones than studying, sitting in discotheques or entertainment venues, hanging out freely without limits, being heavily involved in alcohol and drugs, while also being heavily involved in Therefore, the whole country has been affected by the deterioration in student morality, not only the believer of a single region. The norms of behavior, dress, speech and other aspects of eastern culture are upheld in Muslim-majority nations, yet these are all only symbols of the people's professed faith (Hidayat et al, 2020).…”
Section: Introductionmentioning
confidence: 99%